Physical education´s teacher training program through gaming, ict and continuous assessment - Castañeda-Vázquez, C.; Espejo-Garcés, T.; Zurita-Ortega, F.; Fernández-Revelles, AB. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
This project was carried out Primary Education Degree. The main aim was to increase the students´ levels of motivation and involvement in the subject using gamification strategies, ICT and continuous assessment in the classroom. To this end, a gamification project was developed in the classroom, through ICT and continuous assessment, which is developed in this document. The results showed a high participation of the students (more than 85% of the students participated in the gamification project). Almost 95% of the students attended at the first final exam and 87.9% of the students passed the subject in first call. It was also observed high levels of students´ participation and involvement in the subject, as well as high levels of motivation, both intrinsic and extrinsic, which supposes a positive feedback to consider this innovation as a good educational practice and to continue working in future courses with this type of methodologies.